Development of a portable corona current measuring device for high voltage detection in HVDC systems - Lofrano DOTTO, Fabio ROMANO; Oliveira Conceicao Junior, Pedro; Andreoli, Andre Luiz; De Oliveira Junior, Reinaldo Gotz; Roberto Dos Santos, Benedito Roberto (Institute of Electrical and Electronics Engineers (IEEE), 2022)
The purpose of this work is to present a technological alternative based on the study and development of a simple and portable electronic device to enable the detection and quantification of high voltage and polarity in HVDC systems. The principle of this solution is based on the detection of corona current by means of an aluminum tip held at a distance of about 5 mm from the energized surface through a radial contact rod. The detected electrical current signal is collected and processed through an electronic measuring system. The performance of the proposed device was analyzed by means of corona discharge models and high voltage experimental tests in real-world conditions. The results demonstrated the satisfactory response of the proposed approach in the detection, quantification, and identification of polarity in a 600 kV HVDC transmission system, with an error varying from 1.79% to 2.72% compared to theoretical values, as well as its ability to withstand the influence of temperature variations between 18C to 29C, relative humidity between 56% and 78%, and an atmospheric pressure kept constant at 101.6 kPa. The proposed approach contributes to HVDC monitoring, helping to ensure their operation and suitability and the physical safety of operators.
Keywords: Conductors; Corona; Corona current; Current measurement; DC polarity identification; Discharges (electric); Electric fields; high-voltage direct-current (HVDC); HVDC transmission; measurement system; sensor; Transmission line measurements